Digitalisasi Koperasi Santri untuk Menciptakan Santripreneur - Mahmud Yunus; Haryono Haryono; Sri Suneki; Dwi Prasetiyo Hadi (Universitas Pahlawan Tuanku Tambusai, 2023)
One of the problems faced by the Asshodiqiyah Islamic Boarding School is that the cooperation of students has not been maximized to train students in entrepreneurship. The purpose of this service activity is to solve partner problems through digitizing cooperatives to create entrepreneurs. The method of carrying out activities is with training and assistance in digitizing the business management of santri cooperatives, training, and assistance in digitizing the marketing of santri cooperative business products and training and mentoring to create the character of entrepreneurs. The results of this study indicate that the skills of students have increased in digitizing the business management of students' cooperatives. The santri cooperative already has an online shop at shopee and tokopedia. the character of the entrepreneur soul has increased to 75%